Can serum levels of alkaline phosphatase and phosphate predict cardiovascular diseases and total mortality in individuals with preserved renal function? A systemic review and meta-analysis. - Jing-Wei Li; Cui Xu; Ye Fan; Yong Wang; Ying-Bin Xiao (PLoS ONE, 2014)
It is demonstrated that elevated serum levels of alkaline phosphatase (ALP) and phosphate indicate a higher risks of cardiovascular disease (CVD) and total mortality in population with chronic kidney disease (CKD), but it remains unclear whether this association exists in people with normal or preserved renal function.Clinical trials were searched from Embase and PubMed from inception to 2013 December using the keywords "ALP", "phosphate", "CVD", "mortality" and so on, and finally 24 trials with a total of 147634 patients were included in this study. Dose-response and semi-parametric meta-analyses were performed.A linear association of serum levels of ALP and phosphate with risks of coronary heart disease (CHD) events, CVD events and deaths was identified. The relative risk (RR) of ALP for CVD deaths was 1.02 (95% confidence interval [CI], 1.01-1.04). The RR of phosphate for CVD deaths and events was 1.05 (95% CI, 1.02-1.09) and 1.04 (95% CI: 1.03-1.06), respectively. A non-linear association of ALP and phosphate with total mortality was identified. Compared with the reference category of ALP and phosphate, the pooled RR of ALP for total mortality was 1.57 (95% CI, 1.27-1.95) for the high ALP group, while the RR of phosphate for total mortality was 1.33 (95% CI, 1.21-1.46) for the high phosphate group. It was observed in subgroup analysis that higher levels of serum ALP and phosphate seemed to indicate a higher mortality rate in diabetic patients and those having previous CVD. The higher total mortality rate was more obvious in the men and Asians with high ALP.A non-linear relationship exists between serum levels of ALP and phosphate and risk of total mortality. There appears to be a positive association of serum levels of ALP/phosphate with total mortality in people with normal or preserved renal function, while the relationship between ALP and CVD is still ambiguous.